Detachment and Chemical Characterization of the Regularly Arranged Subunits from the Surface of an Acinetobacter - Thornley, Margaret J. (1974)
Acinetobacter sp. strain MJT/F5/199A carries an array of tetragonally arranged subunits on its outer surface. The subunits can be detached from isolated cell walls by incubation with 1 M urea or by washing with water after treatment with 10 mM ethylenediaminetetraacetic acid or ethyleneglycol-bis(β-aminoethylether)N,N′-tetraacetic acid. After removal of the urea, they reaggregate into the same ordered array at air-water interfaces in the presence of MgCl(2). The detached subunits were characterized as an acidic protein of molecular weight 65,000. They represent one-fifth of the total cell wall protein.